2018
DOI: 10.21873/anticanres.12339
|View full text |Cite
|
Sign up to set email alerts
|

Solarium Use and Risk for Malignant Melanoma: Meta-analysis and Evidence-based Medicine Systematic Review

Abstract: Current scientific knowledge is mainly based on observational studies with poor quality data, which report associations but do not prove causality. At present, there is no convincing evidence that moderate/responsible solarium use increases melanoma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Although there are several previous meta-analyses of the association between indoor tanning device use and skin cancer, the association was mostly based on population-based studies [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several previous meta-analyses of the association between indoor tanning device use and skin cancer, the association was mostly based on population-based studies [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study found that first exposure to sunbeds before the age of 35 years significantly increased the risk of melanoma, the IARC did not find significant evidence for the relation due to the limited number of studies. A recent meta-analysis, including large studies for melanoma published in 2018 [ 18 ] and for NMSC in 2012 [ 19 ], showed a significant association between indoor tanning and the risk of skin cancer. However, this association was mainly confirmed based on the case–control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have consistently established a statistically significant higher risk of cutaneous melanoma with the use of sunbeds (summarized in Table 2 ) [ 18 , 37 , 38 , 39 , 40 , 41 , 42 ]. Nevertheless, the quantification of the measure of the association of sunbed use with melanoma risk is hindered by limitations inherent to the design of individual studies.…”
Section: Sunbed Use and Risk Of Cutaneous Melanomamentioning
confidence: 99%
“…A dose-response relationship has been consistently shown between the amount of sunbed use and the risk of melanoma ( Table 2 ). A significantly higher risk of melanoma was associated with 10 or more annual times of sunbed use [ 37 , 38 , 39 ] and with high [ 18 ] or longest exposure [ 42 ]. The meta-analysis of Boniol et al (2012) reported a 1.8% increase in risk of melanoma for each additional session of indoor tanning per year [ 18 ].…”
Section: Sunbed Use and Risk Of Cutaneous Melanomamentioning
confidence: 99%
“…Some authors hypothesized that indoor tanning could act as a protective factor for melanoma risk, by preventing sunburns. Recently 2 publications expressed scepticism about the carcinogenicity of indoor tanning ( 50 , 51 ). Some authors have used the lack of randomized clinical trials (which would be unethical) to imply that the relationship between sunbed use and melanoma is not causal.…”
Section: Epidemiological Risk Factorsmentioning
confidence: 99%